TRANFORMASI DIGITAL TERHADAP PERUBAHAN PERILAKU PESERTA DIDIK PADA TINGKAT SMP - Safitri, Diana; Qodriyah, Khodijatul; khoiroh, Ummul; Hani’, Ummi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research uses qualitative descriptive methods to explore the impact of digital transformation on changes in student behaviour at SMP Negeri 1 Besuk, Probolinggo Regency. This digital transformation in school learning includes using technology such as Google Classroom, Zoom, and other learning applications that influence learning patterns, social interactions, digital literacy, and students' psychological and emotional aspects. Data was collected through interviews and observations of students, teachers and other related parties. The research results show that digital technology has increased student independence in learning, although several challenges arise related to minimal supervision and withholding technology access. The impact on social interaction shows reduced face-to-face communication between students, while digital literacy has increased, although not evenly. Psychologically, students experience impacts in the form of anxiety and stress triggered by social pressure and excessive use of technology. This research suggests the need for more intensive digital literacy training and wise management of technology to support students' holistic development.Keywords: Transformation, Digital, Behavior.